2011
DOI: 10.1186/1745-6673-6-29
|View full text |Cite
|
Sign up to set email alerts
|

Work-related stress and bullying: gender differences and forensic medicine issues in the diagnostic procedure

Abstract: BackgroundThe attention of international agencies and scientific community on bullying and work-related stress is increasing. This study describes the gender differences found in victims of bullying and work-related stress in an Italian case series and analyzes the critical issues in the diagnostic workup.MethodsBetween 2001 and 2009 we examined 345 outpatients (148 males, 197 females; mean age: 41 ± 10.49) for suspected psychopathological work-related problems. Diagnosis of bullying was established using inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 7 publications
3
31
0
2
Order By: Relevance
“…"Mobbing syndrome" has not yet been described clearly and precisely (11). In ICD-10 and DSM-IV, two conditions which are not particularly associated with work but related to stress are pointed out: the first one is post traumatic stress disorder (PTSD) and the other one is adjustment disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…"Mobbing syndrome" has not yet been described clearly and precisely (11). In ICD-10 and DSM-IV, two conditions which are not particularly associated with work but related to stress are pointed out: the first one is post traumatic stress disorder (PTSD) and the other one is adjustment disorder.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Spain reported stress signs such as headaches, anhedonia, and fatigue among victims (9). Several other studies showed that mobbing causes PTSD (11,15). Mobbing is one of the major causes of suicide (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the world the researches on mobbing have been performed for a long time and the circle of researchers is large enough ([22], [23], [26], [43], [42], [4], [1], [12], [7], [28], [35], [36], [10], [11], [2], [3], [5], [8], [9], [13], [15], [16], [27], [32], [34], [37], [19], etc. ).…”
Section: XVIIImentioning
confidence: 99%
“…In a study conducted in Australia, 50% of the nurses had been exposed to bullying behaviours once or more in the previous year 3. Nowadays, international literature gives accounts of many clinical studies about the ‘mobbing syndrome’, but, despite its economic loss and social importance,4 it does not have a clear nosological definition. Lacking specific diagnostic criteria, the International Classification of Diseases, 10th Revision (ICD-10) and the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR) indicate just two conditions connected to stress that are not necessarily work related: post-traumatic stress disorder (PTSD) and adjustment disorder (AD).…”
Section: Introductionmentioning
confidence: 99%